Small-Molecule Photostabilizing Agents are Modifiers of Lipid Bilayer Properties - Alejo, Jose L. (The Biophysical Society, 2013)
Small-molecule photostabilizing or protective agents (PAs) provide essential support for the stability demands on fluorescent dyes in single-molecule spectroscopy and fluorescence microscopy. These agents are employed also in studies of cell membranes and model systems mimicking lipid bilayer environments, but there is little information about their possible effects on membrane structure and physical properties. Given the impact of amphipathic small molecules on bilayer properties such as elasticity and intrinsic curvature, we investigated the effects of six commonly used PAs—cyclooctatetraene (COT), para-nitrobenzyl alcohol (NBA), Trolox (TX), 1,4-diazabicyclo[2.2.2]octane (DABCO), para-nitrobenzoic acid (pNBA), and n-propyl gallate (nPG)—on bilayer properties using a gramicidin A (gA)-based fluorescence quench assay to probe for PA-induced changes in the gramicidin monomer↔dimer equilibrium. The experiments were done using fluorophore-loaded large unilamellar vesicles that had been doped with gA, and changes in the gA monomer↔dimer equilibrium were assayed using a gA channel-permeable fluorescence quencher (Tl(+)). Changes in bilayer properties caused by, e.g., PA adsorption at the bilayer/solution interface that alter the equilibrium constant for gA channel formation, and thus the number of conducting gA channels in the large unilamellar vesicle membrane, will be detectable as changes in the rate of Tl(+) influx—the fluorescence quench rate. Over the experimentally relevant millimolar concentration range, TX, NBA, and pNBA, caused comparable increases in gA channel activity. COT, also in the millimolar range, caused a slight decrease in gA channel activity. nPG increased channel activity at submillimolar concentrations. DABCO did not alter gA activity. Five of the six tested PAs thus alter lipid bilayer properties at experimentally relevant concentrations, which becomes important for the design and analysis of fluorescence studies in cells and model membrane systems. We therefore tested combinations of COT, NBA, and TX; the combinations altered the fluorescence quench rate less than would be predicted assuming their effects on bilayer properties were additive. The combination of equimolar concentrations of COT and NBA caused minimal changes in the fluorescence quench rate.